4H+15=8-3H

Simple and best practice solution for 4H+15=8-3H equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4H+15=8-3H equation:


Simplifying
4H + 15 = 8 + -3H

Reorder the terms:
15 + 4H = 8 + -3H

Solving
15 + 4H = 8 + -3H

Solving for variable 'H'.

Move all terms containing H to the left, all other terms to the right.

Add '3H' to each side of the equation.
15 + 4H + 3H = 8 + -3H + 3H

Combine like terms: 4H + 3H = 7H
15 + 7H = 8 + -3H + 3H

Combine like terms: -3H + 3H = 0
15 + 7H = 8 + 0
15 + 7H = 8

Add '-15' to each side of the equation.
15 + -15 + 7H = 8 + -15

Combine like terms: 15 + -15 = 0
0 + 7H = 8 + -15
7H = 8 + -15

Combine like terms: 8 + -15 = -7
7H = -7

Divide each side by '7'.
H = -1

Simplifying
H = -1

See similar equations:

| 10x-7=6x-21 | | 11n-3=9n+5 | | 10x-7=6x-12 | | -(9x-3)-(5x-5)+7=-9(x-1)-(9x+9)+3 | | 12+5L=30-4L | | 6x-13-4x=4x-8 | | 100=Y+(Y*.02) | | 5V+3-2V=4V | | 2p-5=27 | | 5y+2(y-6)=7y-2(y-10) | | -4.5b=1.8 | | 6x=21.6 | | 5x-2(x-9)=3(x+1)+3 | | ln(x)=ln(12)-2ln(3) | | 100=Y+(Y*.05) | | x+3=12x-8 | | .24n=95 | | 7=6+2y | | 6+2y= | | x*(18/8-300)-4=-4 | | 3(1+1X)=15 | | 4sin(2*pi*x)=2 | | (4x+9)-(-3x*-3x-5x+9)= | | =p^3-5p^2q-24pq^2 | | 16=-16x^2+32x | | 3(3-1)+(-3*-3)-4= | | 6(6-3)+(-6)-6-4= | | p^3+p^2q-56pq^2= | | 24(-2x+1)=-7(5x+2)-3x | | x-29=87 | | 29+x=87 | | y=5x^2+7 |

Equations solver categories